An Exploratory Case-Study Approach to Understand Multifunctionality in Urban Green Infrastructure Planning in a South African Context - Van Zyl, Burne; Lategan, Louis G.; Cilliers, Elizelle J.; Cilliers, Sarel S. (Frontiers in Sustainable Cities, 2021)
The United Nations Sustainable Development Goals (SDGs) intend to encourage live able urban environments by 2030 with a main focus on strategies to achieve environmental and human well-being. In the same way, central to green infrastructure planning, the multi-functionality principle aims to develop and protect urban green spaces to provide several ecosystem services to increase human well-being whilst protecting the environment. With this in mind, this paper seeks to gather evidence on the nexus between multi-functionality and green infrastructure planning to achieve the SDGs within a South African context. The implementation of green infrastructure to this effect depends on creating awareness of different typologies of green infrastructure elements and the ecosystem services they provide to strengthen the implementation of the green infrastructure concept in urban planning practice. Within the aim of context-specific considerations to green infrastructure planning, green infrastructure typologies possible for implementation within a South Africa urban planning practice context are considerably more limited. A qualitative research approach is employed using case-studies identifying specific examples to explore South African green infrastructure typologies and their multi-functionality. Different multi-functionality concepts are recognized by urban planners in South Africa. The research findings highlighted that multi-functionality achieved through green infrastructure planning should inform urban planning practice to promote the integration of ecological considerations. The paper ultimately provides a deeper insight into the expanding field of green infrastructure research in a South African context by underlining context-based multi-functional green infrastructure typologies and accordingly emphasizes, mainstreaming the ecosystem services concept as part of urban planning practice to address the SDGs locally.